Optimization of inductively coupled plasma mass spectrometer parameter’s to measuring arsenic and selenium - Andrási, Dávid; Puskás-Preszner, Anita; Tarján, Zsuzsa; Kovács, Béla; Győri, Zoltán (Acta Agraria Debreceniensis, 2012)
In the last decades an increased interest has been evolved about arsenic and selenium. The aim is to understand the environmental, agricultural and biological role of the these elements. In case of arsenic the mayor reasons are the relatively high concentration of arsenic in marine biota (mg kg-1) and the arsenic contaminated drinking waterbases of some Asian countries besides Hungary. The toxicity of higher level selenium content is also known, nevertheless selenium is essential for some biological functions. Considering its esssentiality, in our country the insufficient selenium intake rate couse lack of selenium. Measuring the concentrations of these elements are cruital but not satisfactory information, but the speciation, that is the form of an element presented in a sample is also required. In both cases the most suitable method to determine concentration is the inductively coupled plasma mass spectrimetry. My objective was to optimase the changeable parameters of the ICP-MS for reaching the lowest (the best) detection limit. For this porpuse I have investigated the effect of parameter change on nett signal intensity and relative signal intensity. With the optimased parameter settings the limit of detection for arsenic and selenium were determined, which are 0,032 ng cm-3 for arsenic, and 0,097 ng cm-3 for selenium.